Recent Progress of Hollow Carbon Nanocages: General Design Fundamentals and Diversified Electrochemical Applications - Li, Zesheng; Li, Bolin; Yu, Changlin; Wang, Hongqiang; Li, Qingyu (Advanced science, 2023)
Hollow carbon nanocages (HCNCs) consisting of sp2 carbon shells featured by a hollow interior cavity with defective microchannels (or customized mesopores) across the carbon shells, high specific surface area, and tunable electronic structure, are quilt different from the other nanocarbons such as carbon nanotubes and graphene. These structural and morphological characteristics make HCNCs a new platform for advanced electrochemical energy storage and conversion. This review focuses on the controllable preparation, structural regulation, and modification of HCNCs, as well as their electrochemical functions and applications as energy storage materials and electrocatalytic conversion materials. The metal single atoms‐functionalized structures and electrochemical properties of HCNCs are summarized systematically and deeply. The research challenges and trends are also envisaged for deepening and extending the study and application of this hollow carbon material. The development of multifunctional carbon‐based composite nanocages provides a new idea and method for improving the energy density, power density, and volume performance of electrochemical energy storage and conversion devices. In this review, a clear and comprehensive definition of hollow carbon nanocages (HCNCs) is provided. The latest research progress (including preparation, regulation, and modification) of HCNCs in the field of electrochemical energy storages and conversions is detailly reviewed and discussed. The challenges and some insights into new trends and directions for HCNCs are also provided.